THE DEVELOPMENT OF COASTAL AREA AND HUMAN RESOURCE IN BENGKULU PROVINCE - Anzori Tawakal (Jurnal Ilmiah Ekonomi Bisnis, 2022)
This study aims to identify and formulate the potential strategies for developing coastal areas and fisherman human resource strategies in Bengkulu Province - Indonesia. This research was conducted using the sample taken from 18 institutions (i.e., policymakers) and 400 fishermen were randomly selected to participate in the survey. The suggested strategy could be conducted by optimizing the available strengths and opportunities to overcome the existing weaknesses and threats. In particular, it could be done by optimally utilizing the coastal and marine resources to fulfill the broad market share of domestic fisheries products, enforcing the existing laws and regulations, and increasing the level of fish consumption. More specifically, the strategy in regard to fishermen skills development could be choosen to support fisheries production. Thus, leading to the improvement of fishing infrastructure, and the fishermen skills through the utilization of capital assistance from the government’s program.